Analysis of Factors Affecting Distance Learning Using Online Media at PKBM Nurul Islam - Sumiati Sungkono (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Since Covid-19 entered Indonesia, this has had a major impact in various sectors including the education sector. The government has responded responsively since March 2020 to begin distance learning (PJJ). This is done with the aim of inhibiting the spread of the covid-19 virus. The purpose of this research itself is to determine the effectiveness of using online media in distance learning (PJJ) in the non-formal education sector at PKBM Nurul Islam. This study uses the Pieces Framework method which has 6 related indicators, namely performance, information, control / security, efficiency, and service. This study uses a questionnaire via google form which is given online to students. Based on the data obtained through several respondents as a random sample, most of the data obtained by most of the respondents on average support and assess that distance learning is effective for students in PKBM Nurul Islam.